2001
DOI: 10.1021/jo001402s
|View full text |Cite
|
Sign up to set email alerts
|

SelectiveOrthoand Benzylic Functionalization of Secondary and Tertiaryp-Tolylsulfonamides.Ipso-Bromo Desilylation and Suzuki Cross-Coupling Reactions

Abstract: Kinetic vs thermodynamic deprotonation studies on secondary and tertiary sulfonamides 1 and 2 using n-BuLi have been carried out. While both 1 and 2 show kinetic ortho-metalation, thermodynamic conditions lead to ortho and benzylic deprotonation, respectively (Figures 1 and 2). Metalation of 1 using the n-BuLi/KOtBu superbase led to regioselective benzylic metalation (Figure 4); LDA deprotonation was also briefly explored. Application of the developed conditions allows the synthesis of diverse sulfonamide prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In addition, we would like to explore the possibility of using the sulfonyl groups at the 2,2Ј-positions as the directing groups for the functionalization of the 3,3Ј-positions by ortho-lithiation. [8] Resulting dihalide 1e could then serve as a common precursor for a series of 3,3Ј-substituted CSIs. Our approach should provide a more general and convergent synthesis to a wide variety of CSIs with different substituents at the 3,3Ј-positions by using dihalide 1e as the common starting material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we would like to explore the possibility of using the sulfonyl groups at the 2,2Ј-positions as the directing groups for the functionalization of the 3,3Ј-positions by ortho-lithiation. [8] Resulting dihalide 1e could then serve as a common precursor for a series of 3,3Ј-substituted CSIs. Our approach should provide a more general and convergent synthesis to a wide variety of CSIs with different substituents at the 3,3Ј-positions by using dihalide 1e as the common starting material.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the sulfonamide group could serve as a director for ortholithiation in an aromatic system. [8] However, direct lithiation of N-substituted 1d with various organolithium reagents was not successful. The major products were the ringopened products of the sulfonimide, even when a bulky reagent such as tert-butyllithium was used.…”
Section: Resultsmentioning
confidence: 99%
“…McNeil et al 43 smoothly obtained 2-substituted secondary and tertiary sulfonamides in 78-92% yields using iodine as electrophile by quenching the lithio species at both temperatures of -78°C and 0°C (Scheme 62).…”
Section: Scheme 61mentioning
confidence: 99%
“…Aromatic sulfonamides, in turn, were obtained in a three-step procedure starting from commercially available benzenesulfonyl chloride. Ethyl and benzyl groups were introduced in ortho position via metallation-alkylation [13] and Negishi cross-coupling [14], respectively, starting from N-(tert-butyl)benzenesulfonamide (2) [15] ( 3 3a and 3b, resp. ; Scheme 2).…”
mentioning
confidence: 99%